Consumption of ultra-processed foods and food colors by students: a review (Research, Society and Development, 2020)
The aim of the study was to evaluate the consumption of ultra-processed foods and food colors by students. It is an integrative literature review study, the search sources were the databases: Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMED) and Google Scholar. Descriptors used, registered in the descriptors in health sciences (DeCS): "Students", "Food consumption" and "Dyes". The research includes only articles published in the last three years. The search took place in September 2020. 16 references related to the theme were found, of this total, nine references were excluded because they did not fit the inclusion criteria, leaving seven references that fit the study. Among the seven articles found, those published in 2020 prevailed with a total of five articles (71.42%), followed by 2019 and 2018, both with a total of one article (14.29%). It was observed that students are considered large consumers of ultra-processed foods that have chemical additives on their labels. In this sense, it was possible to understand that the consumption of ultra-processed products grows staggeringly, and that it contains chemical additives that can be harmful to health.